Pontos de memória: uma via conceitual de museu no bairro da Terra Firme - GIESE, Silvia Guerreiro (2019)
This Project makes an analysis of the “Ponto de Memória” program, more specifically in its interactions around the Terra Firme neighborhood in Belém, PA – implying Museology‟s sight and linked to social movements. From Museology‟s approach, it was possible to delimit the aspects that define the Program as a public policy from among Museology field of study. Remembering that the current of thought that was spread around the globe in 1960 and 1970 decades, a result of the May 1968 movement, had a direct relation in creating ideological structures inside Museology, which started to vindicate a museum for the people and a popular museology. The “New Museology”, following this direction, influenced many public policies in many countries. In Brazil, the Ponto de Memória program was created in 2009, and so far it is the greatest program sponsored by the federal government that promotes social memory and museological actions inside communities that have been long excluded by the hegemonic logic of culture created by the Elites and exposed in most traditional museums. Terra Firme‟s Ponto de Memória, located in the outskirts of Belém, is one of those actions that, together with MuseuParaenseEmílioGoeldi (EmílioGoeldi Museum), is elaborating activities founded in creating and strengthening the community‟s culture. However, the new types of museums are full of contradictions: facing legal barriers, lack of financial investment and social problems. These are a few of the subjects that matches the difficulty in understanding Integral Museum.